Implementasi Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah pada Usaha Kerajinan Karawo - Radjak, Lukfiah; Falikhatun (Jurusan Akuntansi Politeknik Negeri Malang, 2025)
Abstract: The Implementation of Financial Accounting Standards for Micro, Small, and Medium Entities in Karawo Craft Businesses Purpose: This study aims to examine the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) among Karawo craft MSMEs in Gorontalo. Method: A descriptive qualitative approach was employed, utilizing in-depth interviews with three MSME owners. Findings: The results indicate that MSME actors' understanding of SAK EMKM remains limited due to insufficient socialization, non-accounting educational backgrounds, and non-independent use of the SIAPIK financial recording application. Novelty: This study provides a specific focus on Karawo MSMEs and identifies key barriers to SAK EMKM implementation. Contribution:The research contributes practical recommendations for enhancing socialization, training, and mentoring programs to improve the effective adoption of SAK EMKM. Abstrak: Implementasi Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah pada Usaha Kerajinan Karawo Tujuan: Untuk memahami implementasi Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah (SAK EMKM) pada UMKM kerajinan Karawo di Gorontalo. Metode: Pendekatan kualitatif deskriptif dengan teknik wawancara terhadap tiga pelaku UMKM. Hasil: Menunjukkan pemahaman pelaku UMKM terhadap SAK EMKM masih terbatas akibat kurangnya sosialisasi dan latar belakang pendidikan non-akuntansi, serta penggunaan aplikasi SIAPIK yang belum mandiri. Kebaruan: Fokus spesifik pada UMKM Karawo dan identifikasi hambatan implementasi SAK EMKM. Kontribusi: Rekomendasi peningkatan sosialisasi, pelatihan, dan pendampingan untuk mendorong penerapan SAK EMKM yang lebih efektif.